CALCULATION METHODS OF GAIN FACTORS OF TRANSMITTER AND NOISE RECEIVER ANTENNAS IN ANALYSIS OF ELECTROMAGNETIC COMPATIBILITY - O. I. Korolkova; V. M. Kozel; K. L. Gorbachev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The calculation methods of the gain factors of the transmitter and the interferanthing receiver antennas on the main and cross polarization depending on the true incremental angle and also of the summary antennas gain factor are explained.